Effect of Oral Antidiabetic Agents on Plasma Amylin Level in Patients with Non-insulin-dependent Diabetes mellitus (Type 2) - Zapecka-Dubno, Bożena; Czyiyk, Artur; Dworak, Anna; Bak, Marianna I. (Arzneimittelforschung, 1999)
The purpose of the study was the comparison of the effect of the oral therapy of non-insulindependent diabetes mellitus (NIDDM) with either a sulphonylurea or biguanide derivative on plasma amylin level. In 10 healthy individuals the fasting plasma amylin level was 1.56 ± 0.27 pmol/l (mean ± SEM) and 6 min after i.v. injection of 1 mg glucagon a fourfold increase was observed. In 10 patients with NIDDM receiving glibenclamide (CAS 10238-21-8) the fasting plasma amylin level was twofold higher than in healthy control (2.72 ±, 0.38 pmol/l; p < 0.025) but following glucagon administration it increased only twofold. In 15 patients treated with metformin (CAS 657-24-9) the fasting plasma amylin level was similar to that in healthy individuals (1.64 ± 0.25 pmol/l), but after glucagon stimulation the increment of plasma amylin was minima1 and the relevant mean value was significantly lower when compared with those in healthy individuals and with NIDDM patients treated with glibenclamide.In 10 untreated obese patients with newly diagnosed NIDDM the administration of glibenclamide (14 days) resulted in the increase of basal (2.47 ± 0.23 and 3.16 ± 0.29 pmol/l; p < 0. l), and glucagon stimulated (3.34 ± 0.39 and 4.56 ± 0.38; p < 0.05) plasma amylin concentrations, whereas other 10 patients receiving metformin showed a decrease in fasting plasma level of this peptide before (2.64 ± 0.59 and 1.28 ± 0.38 pmol/l; p < 0. l), and after glucagon injection (5.02 ± 0.55 and 2.83 ± 0.65 pmol/l; p < 0.02). With the respect to the trophic effect of amyloid deposits in the pancreatic islets and to a hypothetic effect of amylin increasing insulin resistance, the present results emphasize the particular usefulness of metformin in the pharmacological treatment of NIDDM. All contraindications and side effects of metformin should be taken into account before drug administration.
Keywords: CAS 657-24-9; CAS 10238-21-8; Diabetes mellitus, non-insulin-dependent; Glibenclamide, clinical studies, effect on plasma amylin level; Metformin, clinical studies, effect on plasma amylin level